Complement component 3 as biomarker of disease activity and cardiometabolic risk factor in rheumatoid arthritis and spondyloarthritis - Iván Arias de la Rosa; Pilar Font; Alejandro Escudero-Contreras; María Dolores López-Montilla; Carlos Pérez-Sánchez; María Carmen Ábalos-Aguilera; Lourdes Ladehesa-Pineda; Alejandro Ibáñez-Costa; Carmen Torres-Granados; Yolanda Jimenez-Gomez; Alejandra Patiño-Trives; María Luque-Tévar; et al. (SAGE Publishing, 2020)
Objective: To analyze the relationship between complement component 3 (C3) and the prevalence of cardiometabolic risk factors and disease activity in the rheumatic diseases having the highest rates of cardiovascular morbidity and mortality: rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA). Methods: This is a cross-sectional study including 200 RA, 80 PsA, 150 axSpA patients and 100 healthy donors. The prevalence of cardiometabolic risk factors [obesity, insulin resistance, type 2 diabetes mellitus, hyperlipidemia, apolipoprotein B/apolipoprotein A (apoB/apoA) and atherogenic risks and hypertension] was analyzed. Serum complement C3 levels, inflammatory markers and disease activity were evaluated. Cluster analysis was performed to identify different phenotypes. Receiver operating characteristic (ROC) curve analysis to assess the accuracy of complement C3 as biomarker of insulin resistance and disease activity was carried out. Results: Levels of complement C3, significantly elevated in RA, axSpA and PsA patients, were associated with the prevalence of cardiometabolic risk factors. Hard clustering analysis identified two distinctive phenotypes of patients depending on the complement C3 levels and insulin sensitivity state. Patients from cluster 1, characterized by high levels of complement C3 displayed increased prevalence of cardiometabolic risk factors and high disease activity. ROC curve analysis showed that non-obesity related complement C3 levels allowed to identify insulin resistant patients. Conclusions: Complement C3 is associated with the concomitant increased prevalence of cardiometabolic risk factors in rheumatoid arthritis and spondyloarthritis. Thus, complement C3 should be considered a useful marker of insulin resistance and disease activity in these rheumatic disorders.